2005
DOI: 10.1139/v05-171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the number of water molecules on the mechanism of N-sulfinylaniline hydrolysis

Abstract: The mechanism of the uncatalyzed hydrolysis of N-sulfinylaniline (Ph-N=S=O) has been studied with B3LYP/6-31+G(2d,2p) in the gas phase, with explicit treatment of water molecules. Hydrolysis involves water attack on sulfur, with a close to perpendicular alignment of a water molecule and the NSO plane in both prereaction complexes and transition states for the rate-determining step. Consequently, the distance of the weak S···O interaction, together with the efficiency of protonation of either nitrogen (attack a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Earlier experimental works conclude that hydroxylation of sulfur is the rate-determining step of hydrolysis. , Modeling of the reaction confirms this conclusion and suggests a concerted mechanism with simultaneous proton transfer to either oxygen or nitrogen of the NSO group. , …”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Earlier experimental works conclude that hydroxylation of sulfur is the rate-determining step of hydrolysis. , Modeling of the reaction confirms this conclusion and suggests a concerted mechanism with simultaneous proton transfer to either oxygen or nitrogen of the NSO group. , …”
Section: Resultsmentioning
confidence: 72%
“…The enthalpy term (Δ H 298 and Δ H ‡ 298, kcal mol −1 ) is used throughout for consistency with our previous papers. , The electronic, unscaled zero-point vibrationally corrected energies, enthalpies and Gibbs free energies of the modeled molecules, complexes and transition states are summarized in Table S1 of the Supporting Information. The averaged entropy contribution − T Δ S is determined to be about 5 kcal mol −1 for reactions across both NS and SO bonds for various N-sulfinyl species, as can be seen from the correlation in Figure S1 of the Supporting Information.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the hydration of heterocumulene, the surrounding water molecules can play the catalytic role by being located mainly in the reactive region and acting as a hydrogen bridge through donating or accepting protons to promote the proton transfer in numerous studies. ,− Furthermore, water molecules can, in addition to taking part in the proton transfer, also interact with each other in the nonreactive region . This explains the catalytic effect of the solvent on the hydration of heterocumulene, such as NHCNH, CO 2 , , COS, CS 2 and Ph-NSO . It was reported that the interaction among the water molecules and the reactant can influence the structures of the stationary points as well as the activation barriers of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…26 This explains the catalytic effect of the solvent on the hydration of heterocumulene, such as NHdCdNH, 27-29 CO 2 , 30,31 COS, 32 CS 2 33 and Ph-NSO. 34 It was reported that the interaction among the water molecules and the reactant can influence the structures of the stationary points as well as the activation barriers of these reactions. For example, in the hydration of COS, due to two other water molecules near the nonreactive oxygen atom, the activation barrier of the rate-determining step can be considerably reduced, from 137.4 kJ/mol in the three-water hydration to 107.9 kJ/mol for the five-water hydration.…”
Section: Introductionmentioning
confidence: 99%